Reporter-Based Screens for the Ubiquitin/Proteasome System - Gierisch, Maria E.; Giovannucci, Tatiana A.; Dantuma, Nico P. (Frontiers in Chemistry, 2020)
Instant and adequate handling of misfolded or otherwise aberrant proteins is of paramount importance for maintaining protein homeostasis in cells. The ubiquitin/proteasome system (UPS) is a central player in protein quality control as it operates in a seek-and-destroy mode, thereby facilitating elimination of faulty proteins. While proteasome inhibition is in clinical use for the treatment of hematopoietic malignancies, stimulation of the UPS has been proposed as a potential therapeutic strategy for various neurodegenerative disorders. High-throughput screens using genetic approaches or compound libraries are powerful tools to identify therapeutic intervention points and novel drugs. Unlike assays that measure specific activities of components of the UPS, reporter substrates provide us with a more holistic view of the general functional status of the UPS in cells. As such, reporter substrates can reveal new ways to obstruct or stimulate this critical proteolytic pathway. Here, we discuss various reporter substrates for the UPS and their application in the identification of key players and the pursuit for novel therapeutics.